2012
DOI: 10.1002/ppap.201200001
|View full text |Cite
|
Sign up to set email alerts
|

Etching and Deposition Mechanism of an Alcohol Plasma on Polycarbonate and Poly(Methyl Methacrylate): An Adhesion Promotion Mechanism for Plasma Deposited a:SiOxCyHz Coating

Abstract: Favourable properties of polycarbonate have led to it replacing glass in many applications; however it does require a protective coating. Plasma deposited protective coatings of amorphous SiOxCyHz have, however, shown marginal adhesion to polycarbonate. This study has shown that plasma pre‐treatments using vapours from the alcohol family improved the coating adhesion on two types of polycarbonate. It is suggested that these plasmas both etch the polycarbonate and deposit a thin plasma polymer layer. It was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…However, under these plasma deposition conditions the coatings were found to be incompatible with some plastic substrates, such as PMMA and PC. [27,48] Coatings deposited at low oxygen concentrations, whilst initially mechanically compliant with the surface, underwent considerable post-plasma reactions, which rendered them less compliant and resulted in coating failure. An alternative must be found wherein mechanically matched, stable coatings can be deposited.…”
Section: Post-plasma Reactionsmentioning
confidence: 99%
“…However, under these plasma deposition conditions the coatings were found to be incompatible with some plastic substrates, such as PMMA and PC. [27,48] Coatings deposited at low oxygen concentrations, whilst initially mechanically compliant with the surface, underwent considerable post-plasma reactions, which rendered them less compliant and resulted in coating failure. An alternative must be found wherein mechanically matched, stable coatings can be deposited.…”
Section: Post-plasma Reactionsmentioning
confidence: 99%
“…Polymers find extensive use in many important modern industries, including automotive, biomedical, environmental, and laboratory applications . Often, however, the properties of the polymer surface, including surface tension and surface functionality, are incompatible with the intended application, thereby limiting their utility.…”
Section: Introductionmentioning
confidence: 99%
“…Often, however, the properties of the polymer surface, including surface tension and surface functionality, are incompatible with the intended application, thereby limiting their utility. Among the most common issues, adhesive failure and delamination are resulting from interface incompatibility, wetting and fouling issues arising from undesirable surface tension or surface functionality, and surface instability causing the polymer surface to denature or degrade . Each of these issues can be mitigated by surface modification processes, including exposure to ultraviolet radiation, flame treatment, and plasma surface modification .…”
Section: Introductionmentioning
confidence: 99%
“…This forms an activated interlayer between the substrate and the coating, with instances of this interlayer being cited elsewhere in pretreatment and adhesions studies . Hall et al previously hypothesised that this interlayer is the primary cause of improved adhesion. It has also been shown that propanol plasma pretreatment processes change the surface properties of the substrate and that a post‐plasma treatment can affect the structure and properties of the coatings .…”
Section: Introductionmentioning
confidence: 96%
“…When depositing these siloxane coatings, it is critical to maximise the adhesion of the coating to the plastic substrate and to this end a treatment of the substrate is often employed . For siloxane coatings, a pretreatment using the vapours from propanol were previously applied to strengthen the adhesion of the coatings, the propanol plasma was shown to both etch and deposit a thin carbon‐based layer .…”
Section: Introductionmentioning
confidence: 99%